Acute laryngeal dystonia: a persisting psychiatric emergency. (October 2016) - May, Robert; Al-Taie, Ali; Garg, Vikas
Objective: Acute laryngeal dystonia is one of the most life-threatening medication side effects in psychiatry. It is rare and predominately caused by the use of antipsychotics in at-risk individuals. Within days of a patient's initial presentation, several antipsychotics can be administered for the purposes of acute sedation and ongoing pharmacotherapy. In this case report, we describe a 27-year-old at-risk male, who developed acute laryngeal dystonia in the context of antipsychotic polypharmacy. Conclusion: Clinicians should take into account recent sedation and ongoing antipsychotic use in patients at risk of developing acute laryngeal dystonia. Awareness of this condition and prompt treatment with parenteral anticholinergic medication can be lifesaving.